if x= (5/8)^-2 into (12/15)^-2 ,then the value of x^-3 is
Answers
Answered by
79
Hi friend, Harish here.
Here is your answer:
Given that,
![x = (\frac{5}{8})^{-2} ( \frac{12}{15})^{-2} x = (\frac{5}{8})^{-2} ( \frac{12}{15})^{-2}](https://tex.z-dn.net/?f=x+%3D+%28%5Cfrac%7B5%7D%7B8%7D%29%5E%7B-2%7D+%28+%5Cfrac%7B12%7D%7B15%7D%29%5E%7B-2%7D++)
To find,
![The\ value\ of \ x^{-3} The\ value\ of \ x^{-3}](https://tex.z-dn.net/?f=The%5C+value%5C+of+%5C+x%5E%7B-3%7D)
Solution:
We know that,
--- (Identity)
Then,
![x = (\frac{5}{8})^{-2} \times ( \frac{12}{15})^{-2} = ( \frac{8}{5})^{2} \times ( \frac{15}{12})^{2} x = (\frac{5}{8})^{-2} \times ( \frac{12}{15})^{-2} = ( \frac{8}{5})^{2} \times ( \frac{15}{12})^{2}](https://tex.z-dn.net/?f=x+%3D++%28%5Cfrac%7B5%7D%7B8%7D%29%5E%7B-2%7D+%5Ctimes+%28+%5Cfrac%7B12%7D%7B15%7D%29%5E%7B-2%7D+%3D+%28+%5Cfrac%7B8%7D%7B5%7D%29%5E%7B2%7D+%5Ctimes+%28+%5Cfrac%7B15%7D%7B12%7D%29%5E%7B2%7D+++)
⇒![x = \frac{8\times 8}{5\times 5} \times \frac{15\times 15}{12\times 12} = \frac{2\times 2}{1\times 1} \times \frac{3\times 3}{3\times 3} = 2\times 2 = 4 x = \frac{8\times 8}{5\times 5} \times \frac{15\times 15}{12\times 12} = \frac{2\times 2}{1\times 1} \times \frac{3\times 3}{3\times 3} = 2\times 2 = 4](https://tex.z-dn.net/?f=x+%3D++%5Cfrac%7B8%5Ctimes+8%7D%7B5%5Ctimes+5%7D+%5Ctimes++%5Cfrac%7B15%5Ctimes+15%7D%7B12%5Ctimes+12%7D+%3D++%5Cfrac%7B2%5Ctimes+2%7D%7B1%5Ctimes+1%7D+%5Ctimes++%5Cfrac%7B3%5Ctimes+3%7D%7B3%5Ctimes+3%7D+%3D+2%5Ctimes+2+%3D+4)
So , x = 4
Then,
![x^{-3} = \frac{1}{x^{3}} = \frac{1}{4^{3}} = \frac{1}{4\times 4\times 4} = \frac{1}{64} x^{-3} = \frac{1}{x^{3}} = \frac{1}{4^{3}} = \frac{1}{4\times 4\times 4} = \frac{1}{64}](https://tex.z-dn.net/?f=x%5E%7B-3%7D+%3D++%5Cfrac%7B1%7D%7Bx%5E%7B3%7D%7D+%3D++%5Cfrac%7B1%7D%7B4%5E%7B3%7D%7D+%3D++%5Cfrac%7B1%7D%7B4%5Ctimes+4%5Ctimes+4%7D+%3D++%5Cfrac%7B1%7D%7B64%7D++)
Therefore the answer is 1 / 64.
_________________________________________________
Hope my answer is helpful to you.
Here is your answer:
Given that,
To find,
Solution:
We know that,
Then,
⇒
So , x = 4
Then,
Therefore the answer is 1 / 64.
_________________________________________________
Hope my answer is helpful to you.
Answered by
15
Step-by-step explanation:
x=(5/8)^-2*(12/15)^-2
x=(8/5)^2*(15/12)^2
x=64/25*125/144
x=4
then the value of x^-3
= 4^-3=(1/4)^3=1/64
Hope this answer is helpful to you
Similar questions